Asymmetric effects of the Covid-19 pandemic on the Ecuadorian labor market: An analysis of job quality in a context of structural heterogeneity - Washington Quintero Montaño; Diego Linthon Delgado; Luis Espinosa Calderón (Revista de Economía del Rosario, 2025)
This paper estimates the microeconomic determinants of job´s quality in Ecuador before and after the Covid-19 pandemic. Using data from the National Employment, Unemployment and Underemployment Survey (ENEMDU) from 2019 and 2021, a job quality variable was created. This variable considers characteristics such as labor income, job stability and labor benefits. The empirical methodology consisted on estimating a Generalized Ordered Response Logistic Model (GOLM). The results show a process of precariousness in the labor market in Ecuador, with younger workers, less-educated workers and ethnic minorities being the most affected. Public policy should design programs for youth employment insertion and the prevention and elimination of labor discrimination.